Determining the optimal lysine to calorie ratio for growth performance of 20- to 50-lb genetiporc nursery pigs - Schneider, J.D.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two studies were conducted to evaluate the effects of increasing dietary lysine and energy density on nursery-pig performance. Exp. 1 was organized as a combination of two simultaneous experiments, with one set of diets consisting of five treatments with increasing TID lysine (0.99, 1.07, 1.14, 1.22, and 1.30%) concentrations, and the second set of diets consisting of five treatments with increasing energy density (1342, 1406, 1471, 1535, and 1600 kcal/lb). The highest l of both lysine and energy density (1.30% and 1600 kcal/lb, respectively) were combined as one diet and used in both the lysine and energy-density titrations to give a total of 10 treatments. Pigs were randomly allotted to 8 replications with 5 pigs per pen on the basis of BW. Overall (d 0 to 21) in Exp. 1 increasing true-ileal-digestible (TID) lysine increased ADG linearly and improved feed efficiency. Although increasing energy density had no effect on ADG, ADFI decreased, which resulted in a quadratic improvement in F/G. Regression analysis of the response surface was used to predict the optimal lysine-to-calorie ratio of 3.65 to 3.71 g lysine/Mcal ME for the Gentiporc pigs used in this experiment. In Exp 2, pigs were fed diets with two different energy densities (1.34 or 1.49 Mcal ME/lb) with TID lysine-to-calorie ratios ranging from 3.1 to 4.1 g/Mcal ME. There was an energy density by TID lysine-tocalorie ratio interaction observed for ADG. Pigs fed the low-energy diets had the greatest ADG at a lysine-to-calorie ratio of 3.60. For pigs fed the high energy diets, ADG improved as the lysine-to-calorie ratio improved to 3.36 g of TID lysine/Mcal ME. There was a quadratic improvement in feed efficiency as the lysine-to-calorie ratios were increased for the pigs fed the low-energy diet, with the best F/G value observed at 3.87; but the pigs fed the high-energy diets had a linear improvement in F/G as the lysine-to-calorie ratios were increased. Although there was a linear improvement in F/G for the high-energy diet, little improvement in feed efficiency was observed when the lysine-to-calorie ratio was increased from 3.36 to 4.07. On the basis of these results, we suggest that the optimal lysine-to-calorie ratio is 3.30 to 3.87 g of TID lysine/Mcal ME for 20- to 50-lb Genetiporc pigs in these facilities.
Keywords: Lysine; Energy; Nursery pigs; Pigs; Swine